Penguatan Perlindungan Hak Anak di Ruang Digital melalui Integrasi Instrumen Hukum Nasional, Internasional, dan Permenkomdigi Nomor 9 Tahun 2026 - Widia Usada; Faisar Ananda (Lembaga Yasin AlSys, 2026)
Strengthening national digital sovereignty is important in mitigating the risks of violence, exploitation, and violations of children’s privacy in cyberspace, particularly through the enactment of Regulation of the Minister of Communication and Digital Number 9 of 2026. This study aims to analyze the synchronization of norms between international legal instruments, particularly the Convention on the Rights of the Child, and national regulations, as well as to explain the child protection mechanisms that must be implemented by Electronic System Providers (PSE). This study used a normative juridical method with statutory and comparative approaches. Secondary data sources included the 1945 Constitution, the Child Protection Law, the Juvenile Criminal Justice System Law, the Convention on the Rights of the Child, and related regulations, which were analyzed qualitatively through content analysis techniques and deductive reasoning. The results showed that Permenkomdigi Number 9 of 2026 harmonizes international standards into national juridical mandates by requiring PSE to implement a safety-by-design approach, an accurate age verification system, and user age-range grouping. The conclusion of this study affirms that the regulation functions as a technical instrument to guarantee the rights to protection, privacy, and growth and development of Indonesian children so that they remain safe and dignified amid the complexity of digital technology transformation. The implications of this study indicate that harmonization among national law, the Convention on the Rights of the Child, and Permenkomdigi Number 9 of 2026 strengthens the framework for protecting children’s rights in the digital space through regulations that are more adaptive to the risks of technology-based violence, exploitation, and privacy violations.